Invasion risk to the United States from Arapaima spp. hinges on climate suitability - Wyman-Grothem, K; Castello, L; Catâneo, DTBS; Doria, CRC; Magalhães, ALB; Patoka, J; Stewart, D; Watson, C (Aquaculture Environment Interactions, 2024)
Fish in the South American genus Arapaima Müller, 1843 (hereafter referred to as arapaimas) have attracted interest for commercial aquaculture development thanks to their rapid growth rate and high market value. However, management agencies in the United States have expressed concerns about importing and culturing arapaimas due to records of non-native establishment in certain other countries where arapaimas were released or escaped from captivity. We used the Freshwater Fish Injurious Species Risk Assessment Model (FISRAM) to estimate the probability that arapaimas would be injurious (able to cause harm) to native ecosystems, humans, or the economy of the contiguous United States. Risk assessment model inputs were elicited from arapaima experts around the world. Model results were sensitive to the estimation of climate suitability for arapaimas within the contiguous United States, with predicted probability of injuriousness ranging from 0.784 down to 0.321 with different climate suitability inputs. Expert assessors predicted that competition and predation on native species would be the most likely mechanism of impact and expressed a high degree of uncertainty about potential for impacts from pathogens and parasites. We concluded that due to the cold sensitivity of these tropically adapted fish, establishment within the contiguous United States would be highly restricted geographically, limiting potential impacts if introduced outside climatically suitable areas. Existing regulations already mitigate risk of escape from aquaculture in areas where establishment is plausible, but further research into arapaima parasites and pathogens would help reduce uncertainties and suggest opportunities to enhance biosecurity measures if needed.